IMPLEMENTASI KEBIJAKAN PERATURAN BUPATI BOGOR NOMOR 6 TAHUN 2018 TENTANG TAMBAHAN PENGHASILAN PEGAWAI - Suminar, Mimin; Rahmawati, Rita; Heryati, Ade (Administratie: Jurnal Administrasi Publik, 2020)
This research is motivated by the issuance of Bogor Regent Regulation number 6 of 2018 concerning Providing Additional Employee Income (TPP) for Civil Servants (PNS) and Candidates for Civil Servants. This research is interesting to study considering that it has only been implemented for more than two years and not many have studied this policy in depth. Therefore, researchers are interested in researching this policy to analyze the implementation of the Additional Employee Income policy in the field whether it is going well or not.The method used in this research uses a descriptive analysis method with a total sample of 52 employees as respondents, with data collection techniques using observation, interviews, questionnaires, and documentation. Then the data were analyzed using the Weight Mean Score (WMS).The results of this study indicate that the value of the implementation of the policy regarding Additional Employee Income is 4.08, the value of this value is interpreted in the good category. This value is by the results of interviews and observations in the field that the respondent feels the benefits of this policy directly to himself and other employees so that he has the enthusiasm to comply with and implement the policy rules issued by this Regent.Suggestions from the results of this study are that the government in making a policy must pay attention to the content of the policy, especially the benefits of the policy that can be felt directly by the object of the policy and improve the character of leadership by superiors so that the policy context can be implemented properly. Keywords: Regulation; Income; Regional Government.ABSTRACTThis research is motivated by the issuance of Bogor Regent Regulation number 6 of 2018 concerning Providing Additional Employee Income (TPP) for Civil Servants (PNS) and Candidates for Civil Servants. This research is interesting to study considering that it has only been implemented for more than two years and not many have studied this policy in depth. Therefore, researchers are interested in researching this policy to analyze the implementation of the Additional Employee Income policy in the field whether it is going well or not.The method used in this research uses a descriptive analysis method with a total sample of 52 employees as respondents, with data collection techniques using observation, interviews, questionnaires, and documentation. Then the data were analyzed using the Weight Mean Score (WMS).The results of this study indicate that the value of the implementation of the policy regarding Additional Employee Income is 4.08, the value of this value is interpreted in the good category. This value is by the results of interviews and observations in the field that the respondent feels the benefits of this policy directly to himself and other employees so that he has the enthusiasm to comply with and implement the policy rules issued by this Regent.Suggestions from the results of this study are that the government in making a policy must pay attention to the content of the policy, especially the benefits of the policy that can be felt directly by the object of the policy and improve the character of leadership by superiors so that the policy context can be implemented properly. Keywords: Regulation; Income; Regional Government.